PUBLIC ADMINISTRATION OF THE SPORT LEISURE IN BRAZIL (Fiep Bulletin - online, 2014)
Public administration in the sport leisure is an ample subject that makes possible some boardings. In this text we carry through a clipping that determined the structure of the text: first we present some sources that argue the promotional State while of social politics, amongst them the sport leisure, using the referencial of Linhales (2001); at as a moment we say on the intervention of the Brazilian State in the sport leisure through a brief historical story, since the decade of 1930 until the current moment; e later we brought the vision of some Brazilian authors (given to its pioneirismo and importance) in the area of the sport leisure in what the public administration says respect.
Keywords: public administration; sport; leisure